Effectiveness of female condom in preventing HIV and sexually transmitted infections: a systematic review protocol. Issue 8 (5th August 2018) - Mome, Ruth KB; Wiyeh, Alison B; Kongnyuy, Eugene J; Wiysonge, Charles Shey
Abstract : Introduction: The HIV pandemic continues to evolve with young women being the most vulnerable group to acquire infection. The presence of sexually transmitted infections (STIs) further enhances HIV susceptibility and also leads to long-term complications such as infertility and cervical cancer. The female condom is a self-initiated method for STI and HIV prevention but there are controversies on its effects. We aim to assess the effectiveness, safety and acceptability of the use of female condoms for prevention of STI and HIV acquisition among women. Methods and analysis: We will search Cochrane Central Register of Controlled Trials, PubMed, EMBASE, Scopus, WHO International Clinical Trials Registry and reference lists of relevant publications for potentially eligible studies. We will screen search outputs, select eligible studies, extract data and assess risk of bias in duplicate; resolving discrepancies through discussion and consensus or arbitration. We will combine data from clinically homogenous studies in a fixed effect meta-analysis and assess the certainty of the evidence using the method for Grading of Recommendations Assessment, Development and Evaluation. We registered the planned systematic review with the International Prospective Register of Systematic Reviews (PROSPERO) in March 2018 and will finalise the search strategy in August 2018; conduct the searches and select eligible studies between August and October 2018; and collect data, conduct statistical analyses and prepare and submit the manuscript for consideration by a peer-reviewed journal between November 2018 and April 2019. Ethics and dissemination: We will use publicly available data; hence no formal ethical approval is required for this review. We will disseminate the findings of this review through conference presentations and publication in an open-access peer-reviewed journal. PROSPERO registration number: CRD42018090710.